2019
DOI: 10.1097/corr.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Patient Age and Hip Morphology Alter Joint Mechanics in Computational Models of Patients With Hip Dysplasia

Abstract: Background Older patients (> 30 years) undergoing periacetabular osteotomy (PAO) to delay THA often have inferior patient-reported outcomes than younger adult patients (< 30 years). It is unclear how patient age affects hip morphology, mechanics, or patient-reported outcome scores. Questions/purposes (1) Is increased patient age associated with computationally derived elevations in joint contact stresses? (2) Does hip shape affect computationally derived joint contact stresses? (3) Do computationally derived j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…First, the DEA methodology used in this study makes numerous simplifying assumptions related to rigid bone, exclusion of the acetabular labrum, and cartilage material properties 46,50 . Furthermore, building DEA models from CT imaging, which does not permit visualization of soft tissues (without the use of a contrast agent), forces researchers to approximate the articular cartilage geometry in most models of dysplastic hips 14,17,21,24,32,46 . Given these limitations of DEA modeling based on clinical CT scans, validation was an important step in our approach.…”
Section: Discussionmentioning
confidence: 99%
“…First, the DEA methodology used in this study makes numerous simplifying assumptions related to rigid bone, exclusion of the acetabular labrum, and cartilage material properties 46,50 . Furthermore, building DEA models from CT imaging, which does not permit visualization of soft tissues (without the use of a contrast agent), forces researchers to approximate the articular cartilage geometry in most models of dysplastic hips 14,17,21,24,32,46 . Given these limitations of DEA modeling based on clinical CT scans, validation was an important step in our approach.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic and Functional Improvement After PAO Compared with other hip-preserving surgeries for patients with DDH, PAO can achieve the ideal positioning of the hip joint rotation center and maintain the inherent stability of the combination of acetabular fragments and residual pelvis, allowing early postoperative weight bearing 21,22 . PAO can effectively resolve both biomechanical and structural abnormalities of the hip joint in patients with DDH, maintain or improve the patient's mobility and quality of life, and delay or prevent the occurrence of secondary osteoarthritis 13,14,23 . This study demonstrated that the overall functional scores of patients after PAO were significantly improved, pain symptoms were significantly reduced, and postoperative radiographic parameters were significantly improved compared with those performed before the operation, which is consistent with the conclusions of other studies 5,12,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The specific osteotomy steps of PAO have been reported in detail in previous literature 5,11,13 . The first step is an incomplete osteotomy of the ischium, starting from the inferior acetabular groove (the posterior lower edge of the acetabulum), using a 30 forked, angled bone chisel, and the osteotomy depth is 2.0-2.5 cm.…”
Section: Osteotomy Steps Of Paomentioning
confidence: 99%
“…Thomas-Aitken and colleagues [11] fit the femoral head and acetabulum to a sphere to quantify the severity of the deformity. This was appropriate given how their research questions were posed, but there are limitations to this approach.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…Of course, the level of complexity necessary for a model to have clinical impact ultimately depends on the research question posed. Thomas-Aitken and colleagues [11] executed a well-designed computational modeling study to test the hypotheses that increased patient age was associated with higher contact stresses, that hip shape affects contact stresses, and that higher contact stresses are associated with higher pain scores (as assessed with the VAS). Based on the results of their discrete-element analysis models, the authors concluded that long-term exposure to elevated cartilage contact stresses may affect joint morphology, making hips in these individuals less amenable to joint-preservation procedures such as PAO.…”
mentioning
confidence: 99%